PENGARUH PENCAMPURAN TEPUNG KACANG MERAH (Phaseolus vulgaris) DAN TEPUNG TERIGU DENGAN PENAMBAHAN EKSTRAK UBI JALAR UNGU (Ipomoea batatas L.) TERHADAP SIFAT SENSORIS MIE KERIN - Siahaan, Bonita; Koapaha, Teltje; Langi, Tineke (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2019)
AbstractThe purpose of this study was to obtain the formulation of dry noodles with a mixture of red bean flour and wheat flour based on the level of acceptance. The statistical design of this experiment was a Completely Randomized Design (CRD) with treatments of the ratio of red bean flour and wheat flour i.e., A (20% red bean flour : 80% wheat flour); B (40% red bean flour : 60% wheat flour); C (60% red bean flour : 40% wheat flour); D (80% red bean flour : 20% wheat flour). Each treatment was repeated 3 times. The results showed that dry noodles preferred by panelists based on color, flavor, and taste was A treatment (20% red bean flour : 80% wheat flour) with the chemical composition and characteristics of that dry noodles was 4.83% water, 1.77% ash, 18.86% protein, 3.18% fat, 71.35% carbohydrates, 7.09 minutes of cooking time, 3.27% cooking loss, 73.20% swelling index, and 261.67% water absorption.Keywords: dry noodles, red bean flour, purple sweet potato